2020
DOI: 10.21203/rs.3.rs-21273/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plastid terminal oxidases in Chlamydomonas: connections with astaxanthin and bio-hydrogen production

Abstract: Background: as a plasto quinol oxidase involved in plastoquinol oxidation in higher plants and microalgae, the plastid terminal oxidase (PTOX) was first recognized in the tomato mutant GHOST (GH) and Arabidopsis mutant IMMUTANS (IM). Genome sequence analysis revealed that duplication of the PTOX gene occurs in certain eukaryotic microalgae, but not in cyanobacteria and most higher plants. PTOX may also be involved in carotenoid synthesis and play a critical protective role against stress, such as high light, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…However, demonstrations of PTOX's involvement in this pathway remain inconclusive, notably because ptox2 Chlamydomonas mutants (see Chlamydomonas AEF mutants strains in Table 1) do not show changes in carotenoids content (Houille-Vernes et al, 2011). This function could be undertaken by PTOX1 (Li et al, 2020) as suggested in the green algae Haematococcus pluvialis (Wang et al, 2009); however, two observations make the role of PTOX in carotenoid synthesis of green algae unclear. Not only the O2 uptake by PTOX during the dark segment of Chlamydomonas' photoperiod is almost null (Strenkert et al, 2019) but, in contrast to plants, most carotenoids seem to be synthesized under light in both Chlamydomonas (Janeiro & Barrnett, 1982) and H. pluvialis (Wang et al, 2009).…”
Section: Chlororespiratory Pathwaymentioning
confidence: 99%
“…However, demonstrations of PTOX's involvement in this pathway remain inconclusive, notably because ptox2 Chlamydomonas mutants (see Chlamydomonas AEF mutants strains in Table 1) do not show changes in carotenoids content (Houille-Vernes et al, 2011). This function could be undertaken by PTOX1 (Li et al, 2020) as suggested in the green algae Haematococcus pluvialis (Wang et al, 2009); however, two observations make the role of PTOX in carotenoid synthesis of green algae unclear. Not only the O2 uptake by PTOX during the dark segment of Chlamydomonas' photoperiod is almost null (Strenkert et al, 2019) but, in contrast to plants, most carotenoids seem to be synthesized under light in both Chlamydomonas (Janeiro & Barrnett, 1982) and H. pluvialis (Wang et al, 2009).…”
Section: Chlororespiratory Pathwaymentioning
confidence: 99%